2022
DOI: 10.1002/adma.202109865
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Hibiscus‐Like Riboflavin/ZIF‐8 Microsphere Composites to Enhance Transepithelial Corneal Cross‐Linking

Abstract: Riboflavin‐5‐phosphate (RF) is the most commonly used photosensitizer in corneal cross‐linking (CXL), but its hydrophilicity and negative charge limit its penetration through the corneal epithelium into the stroma. To enhance the corneal permeability of RF and promote its efficacy in the treatment of keratoconus, novel hibiscus‐like RF@ZIF‐8 microsphere composites [6RF@ZIF‐8 NF (nanoflake)] are prepared using ZIF‐8 nanomaterials as carriers, which are characterized by their hydrophobicity, positive potential, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…On one hand, CXL technology using RF is internationally recognized as the main treatment to prevent and delay the progression of keratoconus [ 23 ]. Accordingly, ROS generated during RF photosensitization mediates the production of new covalent bonds between collagen molecules, leading to an increase in biomechanical strength and stiffness of the corneal stroma [ 24 , 25 ]. The Young's modulus of collagen-based hydrogel has been reported to significantly increase after UV irradiation mediated by RF [ [26] , [27] , [28] ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, CXL technology using RF is internationally recognized as the main treatment to prevent and delay the progression of keratoconus [ 23 ]. Accordingly, ROS generated during RF photosensitization mediates the production of new covalent bonds between collagen molecules, leading to an increase in biomechanical strength and stiffness of the corneal stroma [ 24 , 25 ]. The Young's modulus of collagen-based hydrogel has been reported to significantly increase after UV irradiation mediated by RF [ [26] , [27] , [28] ].…”
Section: Resultsmentioning
confidence: 99%
“…Corneal cross-linking (CXL), an FDA-approved procedure for slowing the progression of keratoconus, uses UV-A light and riboflavin-5-phosphate (RF) to induce cross-linking of collagen [ 23 ]. Reactive oxygen species (ROS) generated during RF photosensitization mediates the production of new covalent bonds between collagen molecules, leading to an increase in biomechanical strength and stiffness of the corneal stroma [ 24 , 25 ]. Of note, RF has a high absorption effect on UV (∼370 nm) rays, preventing most UV light from passing through the cornea.…”
Section: Introductionmentioning
confidence: 99%
“… 35 However, patients involved in this study were relatively milder cases. A novel hibiscus-like microsphere composite RF@ZIF-8 was developed as a carrier to promote riboflavin into the corneal stroma, 36 which presented a better transepithelial CXL effect especially in avoiding the destruction of the cornea. At present, this composite has not been verified in patients with clinical KC.…”
Section: Discussionmentioning
confidence: 99%
“…Three of them, the peak at 132.95, 133.84, and 140.03 eV, respectively, should represent the P 2p 3/2 , P 2p 1/2 , and the Zn 3s or freshly created P−Zn bond, respectively (Figure S3c). 40 The generation of more Zn−O bonds during enzyme loading will improve the structural stability of the hydrolysis of water. 41 Certainly, the high-resolution XPS spectra of Zn 2p showed that the binding energy peaks of each sample were concentrated at 1021.92 (Zn 2p 3/2 ) and 1044.98 eV (Zn 2p 1/2 ) (Figure S3d), which is consistent with the reported Zn-based MOFs, indicating that the different stages of treatment did not cause substantial changes in the structure of ZIF-8.…”
Section: Synthesis and Morphology Analysis Of Crl-n-pvp/ Hzif-8mentioning
confidence: 99%